Analisis Pemahaman Peserta Didik Pada Mata Pelajaran IPS Kelas VIII di SMPK ST. Maria Maumere - Antonia Sari, Fransiska; Nurdin H. Abd. Rahman; Muhammad Shahrun (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to determine students' understanding of social studies at SMPK St. Maria Maumere. This research is a qualitative descriptive study. The subjects of this study were students of SMPK St. Maria Maumere class VIII. The object of this study is an analysis of students' understanding of social studies at SMPK St. Maria Maumere. Data collection techniques and procedures used were observation, interviews and documentation. The results of the study showed that students' understanding of social studies subjects in class VIII at SMPK St. Maria Maumere is categorized as having a good understanding. While the researchers were making observations, interviewing social studies subject teachers and students, that the understanding of students at SMPK St. Maria Maumere was quite good because students quickly responded and understood the material that had been given by the teacher. There are some students who are able to conclude and provide examples related to the learning material taught by the teacher